A second family with CATSHL syndrome: Confirmatory report of another unique FGFR3 syndrome. Issue 7 (3rd May 2016) - Escobar, Luis F.; Tucker, Megan; Bamshad, Michael
Abstract : Here we describe the second reported family with the CATSHL syndrome, a condition resulting from a unique mutation in the fibroblast growth factor receptor 3 ( FGFR3 ) gene. Our family confirms the consistent and unique phenotype of this condition, and the specificity of the mutation in FGFR3 . The CATSHL syndrome appears to be an autosomal dominant disorder with full penetrance. © 2016 Wiley Periodicals, Inc.